2014
DOI: 10.1016/j.envsoft.2014.06.003
|View full text |Cite
|
Sign up to set email alerts
|

A lumped conceptual model to simulate groundwater level time-series

Abstract: ABSTRACT:Lumped, conceptual groundwater models can be used to simulate groundwater level time-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
86
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(86 citation statements)
references
References 64 publications
0
86
0
Order By: Relevance
“…A range of techniques can be used to model groundwater hydrographs at a site, i.e. non-distributed groundwater models, including statistical models (Ahn, 2000;Bloomfield et al, 2003), artificial neural network models (Sreekanth et al, 2009) and "blackbox" models (Mackay et al, 2014). The hydrograph cluster analysis could be used in combination with any of these techniques for groundwater drought forecasting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A range of techniques can be used to model groundwater hydrographs at a site, i.e. non-distributed groundwater models, including statistical models (Ahn, 2000;Bloomfield et al, 2003), artificial neural network models (Sreekanth et al, 2009) and "blackbox" models (Mackay et al, 2014). The hydrograph cluster analysis could be used in combination with any of these techniques for groundwater drought forecasting.…”
Section: Discussionmentioning
confidence: 99%
“…The hydrograph cluster analysis could be used in combination with any of these techniques for groundwater drought forecasting. For example, forecasts of groundwater levels 1 to 3 months out are currently undertaken in the UK for selected sites using a black-box, lumped-parameter model (Jackson et al, 2013;Mackay et al, 2014;Hydrological Outlooks, 2015) driven by probabilistic estimates of future rainfall. Regional inferences of future groundwater levels are then based on qualitative interpretations of the individual sites.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly because ET is a relatively small component of the overall water balance in this catchment and it was not the aim of this study to investigate this aspect of the catchment hydrology. Thirdly, because previous 15 studies have shown that this parameter (and therefore the behaviour of this function) is relatively insensitive and unidentifiable (Mackay et al, 2014).…”
Section: A1 Soil Infiltration and Evapotranspirationmentioning
confidence: 99%
“…Even so, to satisfy the water balance, an explicit representation of the soil zone for model nodes that are not ice or snow-covered was included using the method developed by Griffiths et al (2006) which has been successfully applied to temperate regions in the past (Mackay et al, 2014;Sorensen et al, 2014) and is based on the well 30 established UN Food and Agricultural Organisation soil water balance method (Allen et al, 1998 defines the maximum volume of water available to plants for evapotranspiration after the soil has drained to its field capacity and can be defined from lookup tables with basic information on vegetation and soil information (Allen et al, 1998). This was parametrised using the 'Talus' soil class and 'semi-vegetated' land surface class giving an average T AW value of 7 mm.…”
Section: A1 Soil Infiltration and Evapotranspirationmentioning
confidence: 99%
“…4). Groundwater levels are simulated using the AquiMod lumped conceptual model (Mackay et al 2014), which has been shown to capture nonlinear groundwater level dynamics in a range of hydrogeological settings. Currently, 33 of the AquiMod Gmodels run on a monthly time step and nine on a daily time step, the selection of which has been made considering the degree of variability of the groundwater hydrograph and its responsiveness to rainfall, as determined through analyses of autocorrelation and cross-correlation against rainfall.…”
Section: A National-scale Seasonal Hydrological Forecast Based On Raimentioning
confidence: 99%